2019
DOI: 10.1042/bsr20192502
|View full text |Cite
|
Sign up to set email alerts
|

A novel mass assay to measure phosphatidylinositol-5-phosphate from cells and tissues

Abstract: Phosphatidylinositol-5-phosphate (PI5P) is a low abundance lipid proposed to have functions in cell migration, DNA damage responses, receptor trafficking and insulin signalling in metazoans. However, studies of PI5P function are limited by the lack of scalable techniques to quantify its level from cells and tissues in multicellular organisms. Currently, PI5P measurement requires the use of radionuclide labelling approaches that are not easily applicable in tissues or in vivo samples. In the present study, we d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…Studies have shown that the levels of PI-5-P change in response to various stimuli such as insulin, oxidative stress, bacterial infection etc. and in turn regulate numerous cellular functions such as cell signaling, vesicular transport and even play a role in the nucleus (Hasegawa et al, 2017;Ghosh et al, 2019).…”
Section: Organellementioning
confidence: 99%
“…Studies have shown that the levels of PI-5-P change in response to various stimuli such as insulin, oxidative stress, bacterial infection etc. and in turn regulate numerous cellular functions such as cell signaling, vesicular transport and even play a role in the nucleus (Hasegawa et al, 2017;Ghosh et al, 2019).…”
Section: Organellementioning
confidence: 99%
“…This method enables the quantification of phosphoinositide molecular species in a spectrum of biological samples, including those not amenable to radioisotope labeling. Ghosh et al have also described a mass spectrometry method based on the use of recombinant specific lipid-kinases to in vitro phosphorylate PI3P and PI5P into PI(3,5)P 2 and PI(4,5) P 2 , respectively 8 . However, it still remains a hurdle to simultaneously quantitate the acyl variants of all individual regioisomers of PI-monophosphate (PI3P/PI4P/PI5P) and -bisphosphate [PI (3,4)P 2 /PI(3,5)P 2 /PI(4,5)P 2 ] as well as PI and PI(3,4,5)P 3 in a biological sample 9 .…”
mentioning
confidence: 99%
“…The samples were dried, and reconstituted in 200 μl of methanol. LC MS/MS run method was used as described in Ghosh et al (2019) . The MRM transitions for 37:4 PI4P used was 995.5/613.5 and for 37:4 PI(4,5)P 2 was 1,103.5/613.5.…”
Section: Methodsmentioning
confidence: 99%